1982
DOI: 10.1007/bf00432494
|View full text |Cite
|
Sign up to set email alerts
|

Arbeitsmedizinische untersuchungen �ber ladearbeiten auf einem gro�flughafen

Abstract: In an epidemiologic cross-sectional study, 366 transport workers (age-range: 19-61 years) of a big German airport who are engaged in physical heavy work in unfavorable body positions in narrow freight spaces of airplanes, were investigated with regard to their subjective musculoskeletal complaints through a standardized anamnesis in an interview questionnaire. An additional clinical orthopedic examination was performed in 104 of the transport workers. Back pains were the most frequently reported complaints: at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Andersson et al 1976, Ekholm et al 1982, Nordin 1982, Chaffin & Andersson 1984. However, dysfunction of the knee joint is also, along with that of the other major joints, a common cause of impaired working capacity among unskilled labourers (Undeutsch et al 1982). Mechanical knee joint loads in different standing work situations have not earlier been reported in the literature.…”
Section: Literature Review Knee Load In Different Work Posturesmentioning
confidence: 99%
“…Andersson et al 1976, Ekholm et al 1982, Nordin 1982, Chaffin & Andersson 1984. However, dysfunction of the knee joint is also, along with that of the other major joints, a common cause of impaired working capacity among unskilled labourers (Undeutsch et al 1982). Mechanical knee joint loads in different standing work situations have not earlier been reported in the literature.…”
Section: Literature Review Knee Load In Different Work Posturesmentioning
confidence: 99%
“…The studies referred to another 10 not revealed by the search. Exclusion was made of 15 studies dealing exclusively with self-reported knee trouble (3,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), four studies without a reference group (27)(28)(29)(30), seven studies in which the design was not epidemiologic (8,(31)(32)(33)(34)(35)(36), and one study dealing with an occupational group not exposed to knee load (37). Thus there remained 19 controlled studies with 25 references (4,6,9,, Several of the studies dealt with different types of knee disorders.…”
mentioning
confidence: 99%
“…Lifting, carrying, pulling, and pushing of loads in limited spaces have been found to promote back disorder in airport transport workers. Among workers operating in limited airplane compartment spaces, MSDs were common complaints, with back pain the most frequently reported complaint (among 366 baggage handlers, 66% reported current back symptoms) [55,56]. Other researchers have examined muscle strength in airport transport workers, without investigating MSDs [57], while still others measured postural forces during baggage handling at a large airport, but made no recommendations [58].…”
Section: Airport Baggage Handlersmentioning
confidence: 99%